Tax Compliance Audit: The Perspectives of Tax Auditors in Malaysia - Zandi, Gholam Reza; Elwahi, Abdulrahman Sultan M (Asian Development Policy Review, 2016)
The objective of this paper is to provide an introduction to a tax compliance audit, its processes and problems. Based on the auditor’s perspective regarding tax compliance audits in Malaysia the data gathered and was analyzed. The information collected was strictly based on the viewpoint of tax auditors in Malaysia. The data was gathered from a secondary source and the research methodology was done on a basis of quantitative research based methodology. The Malaysian Inland Revenue Board (IRBM) has significantly increased their focus on tax audits and tax investigations over the past few years. The IRBM recently issued a revised framework for tax audits which replaced the previous tax audit framework. Though the previous tax audit framework was still applicable for petroleum income tax and transfer pricing audits.